CULTURAL VALUES OF GREAT SILK WAY: PAST AND FUTURE - Baltabayeva А. Yu.; Yildiz Naciye; Beskempirova A.U. (Scientific Journal of Pedagogy and Economics, 2019)
This paper considers cultural monuments along the Great Silk Road and actualization of the experience of these objects. Face-to-face methods were used and analyzed to determine the current state of cultural monuments preservation and related folkloric narratives. Historical and archaeological monuments of the Great Silk Road belonging to the Turkestan region have long been the subject of interest, and certain scientific findings have been accumulated, but the peculiarity of its cultivation and it has not been the subject of special research. The methodological base of this paper is the results of surveys from experts and population of Turkestan city. Also in the family as the primary organization of the society a number of recommendations have been made for the further development of national ideas in the spiritual and social consciousness of Kazakhstani people.